Autologous platelet-rich derivatives along with alloplastic bone substitute in the management of complex perio-endo cases - Lata Goyal; Namita Gupta; Narinder Dev Gupta (Wolters Kluwer Medknow Publications, 2020)
Combined endodontic periodontal lesion is one of the most challenging dental conditions as making a definite diagnosis and henceforth treatment plan is a daunting task. The prognosis of complex lesion involving both endodontic and periodontic components is complex, but success rate can be improved with regenerative therapies. However, there is paucity of literature regarding its effectiveness in the clinical scenario as only few case reports have been documented in literature for the use of platelet-rich derivatives in regenerative osseous surgery requiring both endodontic and periodontal treatment. We are hereby presenting three cases requiring both endo and perio treatment. The first two cases involve mandibular first molar and maxillary first molar, respectively. The third case involves maxillary central incisor. In all the cases, first, endodontic treatment was initiated, then open flap curettage along with alloplastic bone substitutes was done. Platelet-rich fibrin and platelet-rich plasma were used along with. Three of the treated cases showed significant improvement radiographically and clinically. There was gain in clinical attachment, reduction in probing depth, and radiographic bone fill. Autologous platelet-rich derivative can be used in combination with alloplastic bone substitute for the management of endo-perio cases. Further long-term studies are needed to explore the clinical effectiveness of platelet-rich derivatives and predicting the probability of success of periodontal therapy.